Quality attributes of fufu in south-east Nigeria: guide for cassava breeders - Chijioke, Alamu Ugo; Madu, Tessy; Okoye, B.; Ogunka, A.M.; Ejechi, M.; Ofoeze, M.; Ogbete, C.; Njoku, D.; Ewuziem, J.; Confidence, K.; Onyemauwa, N.; Ukeje, B.; et al. (Wiley, 2020)
Fufu is a popular traditional fermented wet paste food product from cassava. We examined consumer preferences and quality attributes of fufu in Abia and Imo States of South‐East Nigeria, with special attention to gender differences, for the purpose of providing guidance to breeders. Data were analysed by the use of descriptive and inferential statistics. Participants for the interview were randomly selected from a list of farmers in the study area. Individual (II) interviews were conducted among eighty participants comprising twenty‐six men (32.5%) and fifty‐four women (67.5%). Preferences along the food chain from raw roots to final product were also obtained. Major traits influencing gender‐specific consumer preferences are related to appearance, texture and smell. Smoothness, not sticky, easy to swallow and drawability of fufu appear to be major traits that drive acceptance by both men and women. Big roots and smooth skin are prioritised for raw material. Some quality characteristics are conditioned largely by variety traits, while others can be modified by adjusting the processing methods. The complexity of producing high‐quality fufu makes it imperative to introduce a multidisciplinary approach into breeding programmes.